Evropske ideje iz Galicije za razvoj gozdarskega izobraževanja v Sloveniji - Bogataj, Nevenka (Gozdarski vestnik, 2008)
The lifelong adult education in the field of sustainable forest management gains importance in Europe. The Forest Action Plan (EU 2006) in its fifth key measure explicitly lists the need for supporting the cooperation among forest owners and enhancing the education and training in forestry. These contents are also dealt with in the project Leonardo da Vinci "European Ideas for the Development of Forest Owners Education in Slovenia", taking place at SlovenianForestry Service. The representatives of five Slovenian institutions were getting to know European ideas in 2007 in Galicia, one of the seventeen autonomous regions in Spain. Galicia's surface, population and forest coverageis comparable to Slovenia. However, historical, cultural, geographicaland climatic conditions add a new dimension to the comparisons. A high percentage of private forests with extremely fragmented propriety structure, important influence of fire danger and changed composition with fast growing foreign tree species are the factors affecting the organization of forestry institutions, educational programs, forest management and protection and the role of forestry-based economy branches. Presented are: forest management on the example of forest owners' organization, education on the University of Vigo including information and communication technologies, strategic approaches of the regional Ministry responsible for forests and the forest owners association "Silvanus". Regardless of the differences the forestry challenges in Slovenia and Galicia are comparable and therefore the goals are often similar: focusing on a higher effectiveness of forest management, organized cooperation of owners, activating them; placing the forestry in both local problematic and global environmental challenges and orientation of the forestry toward the education and communication not only with the nature, but also with people.
Keywords: Lifelong learning; vseživljenjsko učenje; education; izobraževanje; gozdarstvo; forestry; Slovenia; Slovenija; Galicija